Land use change and greenhouse gas emissions: an explanation about the main emission drivers - Lima Abreu, Natan [UNESP]; da Cruz Ribeiro, Eleanatan Syanne; de Sousa, Camila Eduarda Souza [UNESP]; Maués Moraes, Lorena; de Oliveira, João Victor Costa; de Abreu Faria, Letícia; Cláudia Ruggieri, Ana [UNESP]; da Silva Cardoso, Abmael; Faturi, Cristian; do Rêgo, Aníbal Coutinho; da Silva, Thiago Carvalho (FapUNIFESP (SciELO), 2024)
Global warming is attributed to the increase in greenhouse gas (GHG) emissions, such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O). Land use changes significantly impact on GHG emissions, accounting for approximately 44% of the country’s emissions in 2019. This review addresses the main pathways of GHG formation in the soil, focusing on the influence of land use changes on GHG emissions. It is found that soil CO2 emissions are related to root respiration, microorganisms, and organic matter (OM) decomposition in the soil. Changes in land use can alter soil characteristics, favoring increased CO2 emissions. Soil CH4 emissions occur under anaerobic conditions by methanogenic microorganisms; however, land use changes, such as forest conversion to pasture, can increase CH4 emissions due to a higher concentration of methanogenic microorganisms in the soil. On the other hand, N2O is produced in the soil during nitrification and denitrification processes by microorganisms, and nitrogen fertilization in agricultural areas can increase N2O emissions, especially when associated with soil moisture and the availability of organic carbon. It is important to understand the dynamics of GHG formation and emissions resulting from land use changes because efficient management strategies can reduce these emissions and contribute to Brazil’s goals for GHG reduction as established in international agreements.
Mudanças de uso da terra e emissão de gases de efeito estufa: uma explanação sobre os principais drivers de emissão
Keywords: Carbon stock; methane in the soil; nitrous oxide in the soil